Beneath the raptor’s wings : the avian composition grasping the symbol for eternity in Egypt - Klop, Damian J. R. (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MPhil (Ancient Studies)--University of Stellenbosch, 2008.